Physiological Response of Three Grapevine Cultivars Grown In North-Western Poland to Mycorrhizal Fungi - Mikiciuk, G.; Sas-Paszt, L.; Mikiciuk, M.; Derkowska, E.; Trzciński, P.; Ptak, P.; Chylewska, U.; Statkiewicz, M.; Lisek, A. (South African Journal of Enology and Viticulture, 2018)
West Pomerania (Poland) is located near the northern boundary of the range of viticulture (the coldest zone A). Unfavourable weather conditions can pose a serious threat to the cultivated vines. One of the treatments used to increase the tolerance of plants to abiotic and biotic stresses is inoculation with symbiotic soil microorganisms. This paper focuses on the influence of mycorrhization on the changes in soil microbiology, the degree of colonization of roots by mycorrhizal fungi, and on selected physiological parameters of three grapevine cultivars (‘Pinot Noir’ on SO4 rootstock, ‘Regent’ on 5BB rootstock, and ‘Rondo’ on 125AA rootstock). The applied inoculation had a stimulating effect on the colonization of roots by arbuscular mycorrhizal (AM) fungi, as evidenced by higher mycorrhizal frequency and intensity in the mycorrhized plants. The mycorrhizal treatment increased the intensity of CO2 assimilation and transpiration. Mycorrhization reduced the efficiency of photosynthetic water use and increased stomatal conductance for water in the grapevines tested. The mycorrhizal treatment did not affect the concentration of assimilation pigments in vine leaves. The mycorrhization of grapevines had no effect on the values of initial fluorescence, maximum fluorescence, the maximum potential efficiency of photochemical reaction in PS II, the size of the pool of reduced electron acceptors in PS II, nor on the value of the PS II vitality index.